Are Personality-Based Intellectual Styles Culture Specific or Universal? - Zhang, Li-fang (Frontiers in Psychology, 2021)
Traditionally, it had been commonly believed that individuals in the same culture have personalities distinct from those of individuals in other cultures. This article examines this belief by critically reviewing relevant literature generated from two of the most widely investigated personality-based style constructs in the field of intellectual styles: the Jungian personality styles and the career personality styles proposed by Holland. It aims at answering the question of whether personality-based intellectual styles are culture specific or they are universal. To achieve this aim, based on the two broad cultural systems derived from Hofstede’s model of four cultural dimensions and two major style types from Zhang and Sternberg’s threefold model of intellectual styles, two research hypotheses were made. To test the hypotheses, two types of empirical literature centered on each of the two personality-based styles are reviewed: 1) cross-cultural comparative studies; and 2) within-culture studies investigating the association of the two style constructs with other human attributes and outcomes. Results suggest that although personality-based styles are related to culture, they cannot be culture specific; rather, they are fundamentally universal. These findings carry scientific value and have practical implications for education and beyond.